2019
DOI: 10.1186/s12967-019-1792-8
|View full text |Cite
|
Sign up to set email alerts
|

New risk score for predicting progression of membranous nephropathy

Abstract: BackgroundPatients with Idiopathic membranous nephropathy (IMN) have various outcomes. The aim of this study is to construct a tool for clinicians to precisely predict outcome of IMN.MethodsIMN patients diagnosed by renal biopsy from Shanghai Ruijin Hospital from 2009.01 to 2013.12 were enrolled in this study. Primary outcome was defined as a combination of renal function progression [defined as a reduction of estimated glomerular filtration rate (eGFR) equal to or over 30% comparing to baseline], ESRD or deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Primary membranous glomerulonephritis (MGN) is one of the most common types of primary glomerulonephritis among adults [1,2], associated with a frequent increase in prevalence in Southeast Asia [3] and Malaysia [4] in particular. Although biopsy remains the confirmatory test for MGN, the clinical outcome is variable and often unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…Primary membranous glomerulonephritis (MGN) is one of the most common types of primary glomerulonephritis among adults [1,2], associated with a frequent increase in prevalence in Southeast Asia [3] and Malaysia [4] in particular. Although biopsy remains the confirmatory test for MGN, the clinical outcome is variable and often unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…chronic kidney disease (cKd) is becoming a serious public health problem because it is related to an increased risk of cardiovascular disease and mortality (1)(2)(3)(4). as one of the main types of cKd, membranous nephropathy (Mn), is an autoimmune disease characterized by diffuse deposition of immune complexes under glomerular epithelial cells (Gecs), with diffuse thickening of the glomerular basement membrane (GBM) (5,6). according to primary diseases, Mn can be categorized into idiopathic membranous nephropathy (iMn) and secondary membranous nephropathy (SMn), while iMn accounts for approximately 80% of the total incidence of Mn (7).…”
Section: Introductionmentioning
confidence: 99%
“…Because iMN occurs frequently in older patients, many investigators are interested in the relationship between renal outcomes and age. Although some studies have shown that older patients with iMN had a poor prognosis [ 8 , 16 , 17 ], a recent study that analyzed Japanese data showed that younger and older patients with iMN had similar renal outcomes [ 15 ]. Generally, at the time of biopsy, the initial eGFR is lower in older patients than in younger patients; consequently, older patients might reach renal failure faster than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to proteinuria levels, age and eGFR have been reported as predictors of outcome in patients with iMN. Although younger and older patients with iMN had comparable renal outcomes in a recent Japanese multicenter study [15], other studies showed that older age was associated with inferior renal survival [8,16,17]. A low eGFR at disease presentation was also reported to be associated with poor renal outcomes [16,18].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation